Improving the Mechanical and Interfacial Properties of Bhendi Fiber via Chemical Surface Treatments - Haydar U. Zaman (International Journal of Advance in Molecular Engineering, 2025)
Because of its primary benefits—moderate strength and stiffness, low cost, and being a renewable, degradable, and ecologically friendly material—natural fibers are believed to have potential use as reinforcing agents in polymer composite materials. Due to their inherent hydrophilicity, they have a tendency to retain moisture, which can impair or soften the fibers' adhesion to the surrounding matrix. This can have an impact on the performance of composite materials used in environments with high relative humidity, particularly when temperatures are high. Fiber surface treatments are commonly used to strengthen the connection between the fibers and matrix. In order to increase the mechanical, morphological, and structural characteristics of Bhendi fibers' compatibility with polymer matrix, the effects of alkali, silane, and combination alkali and silane treatments were investigated. By using scanning electron microscopy (SEM) examination, it was demonstrated that the saline and alkali treatments were successful in removing contaminants from the fiber surfaces. Silane-treated Bhendi fibers have fewer impurities, lignin, and hemicelluloses removed than those treated with other chemicals, according to the SEM morphological study of treated Bhendi fibers. The droplet test findings show that the fibers treated with alkali and alkali-silane had better interfacial stress strength, whereas the Bhendi fiber treated with silane had the highest interfacial stress strength. The development of high-performance Bhendi fiber reinforced polymer composites for industrial applications is anticipated to be aided by fiber treatments.
Keywords: Bhendi fiber; Epoxy resin; chemical treatments; droplet test; fiber-matrix interfacial adhesion; tensile properties